Church-Based Social Support, Functional Disability, and Change in Personal Control over Time - Krause, Neal M. (Journal of religion and health, 2014)
The purpose of this study is to see whether measures of church-based and secular social support offset the effects of functional disability on change in feelings of personal control over time. Survey data were obtained from Wave 2 and Wave 3 of a nationwide sample of older adults (N = 583). The findings suggest that spiritual support from fellow church members offsets the effects of functional disability on change in feelings of personal control over time. In contrast, neither emotional support from fellow church members nor emotional support from secular social network members exerted a similar effect.